Capsid-CPSF6 Interaction Is Dispensable for HIV-1 Replication in Primary Cells but Is Selected during Virus Passage In Vivo - Saito, Akatsuki (J Virol, 2016)
Cleavage and polyadenylation specificity factor subunit 6 (CPSF6), a host factor that interacts with the HIV-1 capsid (CA) protein, is implicated in diverse functions during the early part of the HIV-1 life cycle, including uncoating, nuclear entry, and integration targeting. Preservation of CA binding to CPSF6 in vivo suggests that this interaction is fine-tuned for efficient HIV-1 replication in physiologically relevant settings. Nevertheless, this possibility has not been formally examined. To assess the requirement for optimal CPSF6-CA binding during infection of primary cells and in vivo, we utilized a novel CA mutation, A77V, that significantly reduced CA binding to CPSF6. The A77V mutation rendered HIV-1 largely independent from TNPO3, NUP358, and NUP153 for infection and altered the integration site preference of HIV-1 without any discernible effects during the late steps of the virus life cycle. Surprisingly, the A77V mutant virus maintained the ability to replicate in monocyte-derived macrophages, primary CD4(+) T cells, and humanized mice at a level comparable to that for the wild-type (WT) virus. Nonetheless, revertant viruses that restored the WT CA sequence and hence CA binding to CPSF6 emerged in three out of four A77V-infected animals. These results suggest that the optimal interaction of CA with CPSF6, though not absolutely essential for HIV-1 replication in physiologically relevant settings, confers a significant fitness advantage to the virus and thus is strictly conserved among naturally circulating HIV-1 strains. IMPORTANCE CPSF6 interacts with the HIV-1 capsid (CA) protein and has been implicated in nuclear entry and integration targeting. Preservation of CPSF6-CA binding across various HIV-1 strains suggested that the optimal interaction between CA and CPSF6 is critical during HIV-1 replication in vivo. Here, we identified a novel HIV-1 capsid mutant that reduces binding to CPSF6, is largely independent from the known cofactors for nuclear entry, and alters integration site preference. Despite these changes, virus carrying this mutation replicated in humanized mice at levels indistinguishable from those of the wild-type virus. However, in the majority of the animals, the mutant virus reverted back to the wild-type sequence, hence restoring the wild-type level of CA-CPSF6 interactions. These results suggest that optimal binding of CA to CPSF6 is not absolutely essential for HIV-1 replication in vivo but provides a fitness advantage that leads to the widespread usage of CPSF6 by HIV-1 in vivo.